Twentieth-Century Art from the Nelson Aldrich Rockefeller Collection - Wheeler, Monroe; Rockefeller, Nelson A.; Lieberman, William S. (New York : The museum of Modern Art, 1969)
Arp, Jean ; Giacometti, Alberto ; Matisse, Henri ; Picasso, Pablo ; Gris, Juan ; Miro, Joan ; Schwitters, Kurt ; Trova, Ernst ; etc.
Twentieth-Century Art from the Nelson Aldrich Rockefeller Collection, The Museum of Modern Art, New York, May 26 through September 1, 1969
Engels
kunstcatalogus